Full-length transcriptome analysis identifies SpRCC1 as a positive regulator of growth in Spathiphyllum kochii - Lin, Huifeng; Wang, Xuanting; Xu, Kezheng; Ni, Zhi; Li, Lihong; Zhou, Huiming; Lin, Fazhuang; Xu, Xuming; Xiao, Jiajing; Zhu, Nanyan; Ge, Danfeng; Xu, Weifeng (Frontiers in Plant Science, 2026)
Plant architecture is a critical agronomic trait that directly influences both the ornamental and commercial value of horticultural crops. Spathiphyllum kochii, a perennial evergreen herbaceous plant in the Araceae family, includes a naturally occurring dwarf mutant, Meibian’, which provides a valuable genetic resource for elucidating the molecular mechanisms controlling plant stature. In this study, we constructed a high-quality, full-length reference transcriptome based on the standard cultivar ‘Meijiu’ and its dwarf mutant ‘Meibian’ using PacBio Iso-Seq platforms. De novo assembly yielded 122,346 non-redundant high-confidence transcripts, including 94,809 predicted protein-coding sequences, of which 85,055 (89.71%) were successfully annotated in public databases. Phenotypically, ‘Meibian’ exhibits markedly reduced leaf, petiole, spathe, and spadix size compared to ‘Meijiu’. Transcriptome profiling across these four tissues identified 2,660 differentially expressed genes, with a global trend toward transcriptional repression in the dwarf mutant. Weighted Gene Co-expression Network Analysis revealed a key module significantly correlated with the dwarf phenotype, enriched in cytokinin-responsive genes and negative regulators of molecular functions. Among the hub genes, Spathiphyllum kochii Regulator of Chromosome Condensation 1 (SpRCC1) was identified as a potential key regulator. Full-length cloning confirmed a 2,303 bp coding sequence encoding a conserved RCC1 domain protein localized in the nucleus. Expression analysis showed significantly lower SpRCC1 expression in ‘Meibian’, consistent with transcriptome data. Overexpression of SpRCC1 in Arabidopsis thaliana resulted in increased leaf area, supporting its positive role in promoting growth. This study provides the first functional evidence linking SpRCC1 to plant architecture regulation in Spathiphyllum and establishes a valuable transcriptomic resource for molecular breeding of compact ornamental cultivars.